THE ROLE OF SOCIAL ENTREPRENEURSHIP IN SOLVING THE PROBLEM OF YOUTH UNEMPLOYMENT - ACHKASOVA, Oksana (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The research is devoted to one of the critical problems of the employment of the population of Ukraine today, namely the problem of youth unemployment, which became even more acute during the martial law. An analysis of the indicators characterizing the employment of Ukraine's youth and their quantitative and qualitative characteristics was carried out, thanks to which we can ascertain the high level of youth unemployment. The specifics of the youth's age-specific socio-psychological and qualification features as the most unprepared for the current complex state of the labor market and one of the most vulnerable parts of the workforce in Ukraine are described. Official statistical data on youth unemployment are presented, and a comparative analysis of youth unemployment during martial law is made. The results of sociological research on the entrepreneurial orientations of modern youth were analyzed, and the desire of most young people to start their own businesses was emphasized. The problems that arise when opening a business for young people are considered, namely, the need for own funds and opportunities for obtaining a loan, as well as the sufficiency of work experience in the relevant field. The possibility of improving the employment situation of Ukrainian youth is considered, in particular, based on the development of youth entrepreneurship and the use of an innovative business model such as social entrepreneurship. The features of social entrepreneurship in Ukraine and the current state of its development are defined and considered. The advantages and opportunities that social entrepreneurship opens for modern youth to realize their business ideas and overcome youth unemployment in the domestic labor market have been established. Information is provided on the possibilities of self-information about social entrepreneurship, and the main differences between social entrepreneurship and ordinary types of economic activity are indicated.
Keywords: youth unemployment; employment; economic activity; youth entrepreneurship; social entrepreneurship